You are what you eat: How to best fuel your immune system - Hellmich, Charlotte; Wojtowicz, Edyta E. (Frontiers in Immunology, 2022)
Normal bone marrow (BM) homeostasis ensures consistent production of progenitor cells and mature blood cells. This requires a reliable supply of nutrients in particular free fatty acids, carbohydrates and protein. Furthermore, rapid changes can occur in response to stress such as infection which can alter the demand for each of these metabolites. In response to infection the haematopoietic stem cells (HSCs) must respond and expand rapidly to facilitate the process of emergency granulopoiesis required for the immediate immune response. This involves a shift from the use of glycolysis to oxidative phosphorylation for energy production and therefore an increased demand for metabolites. Thus, the right balance of each dietary component helps to maintain not only normal homeostasis but also the ability to quickly respond to systemic stress. In addition, some dietary components can drive chronic inflammatory changes in the absence of infection or immune stress, which in turn can impact on overall immune function. The optimal nutrition for the best immunological outcomes would therefore be a diet that supports the functions of immune cells allowing them to initiate effective responses against pathogens but also to resolve the response rapidly when necessary and to avoid any underlying chronic inflammation. In this review we discuss how these key dietary components can alter immune function, what is their impact on bone marrow metabolism and how changes in dietary intake of each of these can improve the outcomes of infections.